An Investigation into the Antecedent and Consequences of Value Co-Creation in Fitness Services (Third Sector Social Economic Review, 2025)
Today, customers are considered both producers and consumers of services, and their participation in the service process provides significant value to both businesses and customers. In fitness centers, this participation takes the form of responsible, advocacy, and helping behaviors, influenced by members’ self-efficacy. This study examined the antecedents and consequences of value co-creation behaviors among fitness service users. Self-efficacy was modeled as the antecedent variable, while customer loyalty, satisfaction with sport life, and life satisfaction were specified as outcome variables. Data were collected from 384 fitness center members in Istanbul, Ankara, Izmir, and Eskisehir (minimum one month of experience) using purposive sampling and a questionnaire, and analyzed via structural equation modeling. Results showed that self-efficacy fosters responsible, advocacy, and helping behaviors. Only advocacy significantly enhanced customer loyalty, whereas all three behaviors increased sport life satisfaction and life satisfaction. Sport life satisfaction further improved both life satisfaction and loyalty. The findings suggest that customer participation contributes not only to economic outcomes but also to individual well-being, emphasizing the multifaceted value of co-creation in fitness services.
Keywords: Value Co-Creation; Self-Efficacy; Customer Loyalty; Life Satisfaction; Fitness Services